Strategi Generik Porter Dalam Meningkatkan Daya Saing Sekolah Di MTS Khoirul Kasbi Desa Paldas - Ika lenaini; Kasinyo Harto; Helen Sabera Adib; Saipul Annur (JURNAL KAJIAN ISLAM MODERN, 2023)
This study aims to describe Porter's Generic strategy in increasing school competitiveness, to analyze what are the inhibiting and supporting factors for implementing Porter's Generic strategy in increasing school competitiveness, and to analyze the impact of Porter's Generic strategy in increasing school competitiveness at MTs Khoirul Kasbi. The approach used in this study is a qualitative approach. Data collection techniques used include: observation, interviews and documentation. Data analysis techniques used by researchers by carrying out several steps including: reading, reading and reading, coding, giving meaning, developing various relationships, and writing the results of the analysis into a story. The results of this study indicate that MTs Khoirul Kasbi has implemented the concepts of Porter's Generic strategy, namely the Cost Leadership Strategy by reducing educational costs, even MTs Khoirul Kasbi provides free tuition to students, while from the differentiation strategy Mts Khoirul Kasbi has implemented the tahfidz Qur' superior program an and reading of the Yasin surah which is carried out before starting the learning process, and the focus strategy of MTs Khoirul Kasbi focuses more on or improves the Tahfidz Qur'an program with the aim of increasing students who have good morals. As for the inhibiting factors, namely: Lack of student interest in implementing the flagship program (Tahfiz Qur'an program), and many students cannot read the Qur'an. But this inhibiting factor is not an obstacle in the effort to implement Porter's Generic strategy because this can be overcome by the school so that it can run as expected. While the supporting factors are: Unique Skills, High enthusiasm from students, Adequate facilities, and good teacher performance. With the implementation of Porter's Generic strategy, it has a very positive impact on developments at MTs Khoirul Kasbi, such that many people are interested in sending their children to MTs Khoirul Kasbi, thus the number of students at MTs Khoirul Kasbi continues to increase every year.